The Open Government and People Engagement in State Management - Giao, Vu Cong; Thu, Le Anh (VNU Journal of Science: Legal Studies; Vol 36 No 4DO - 10.25073/2588-1167/vnuls.4316, 2020)
In order to mobilize people's involvement in the state management in a practical, effective and sustainable manner, appropriate strategies and measures are required. One of the most comprehensive and effective measures among which is applying the Open Government model. The paper analyzes theoretical asspects and best practices of some countries on the relationship between citizen involvement and the open government model, thereby draws some suggestions for Vietnam in applying this model to promote and improve the efficiency of people's engagement in state management in Vietnam in the coming years.